PENYELESAIAN MULTI TRAVELING SALESMAN PROBLEM DENGAN ALGORITMA GENETIKA - MAYULIANA, NI KADEK; KENCANA, EKA N.; HARINI, LUH PUTU IDA (E-Jurnal Matematika; Vol 6 No 1 (2017)DO - 10.24843/MTK.2017.v06.i01.p141, 2017)
Genetic algorithm is a part of heuristic algorithm which can be applied to solve various computational problems. This work is directed to study the performance of the genetic algorithm (GA) to solve Multi Traveling Salesmen Problem (multi-TSP). GA is simulated to determine the shortest route for 5 to 10 salesmen who travelled 10 to 30 cities. The performance of this algorithm is studied based on the minimum distance and the processing time required for 10 repetitions for each of cities-salesmen combination. The result showed that the minimum distance and the processing time of the GA increase consistently whenever the number of cities to visit increase. In addition, different number of sales who visited certain number of cities proved significantly affect the running time of GA, but did not prove significantly affect the minimum distance.
Keywords: Genetic Algorithm, Multi Traveling Salesman Problem, simulation